ఆధునిక భారతదేశంలో కులం ఇతర వ్యాసాలు - Srinivas, M.N. (My University, 2019)
Through this book, the author has emphasized on 'empirical studies' and 'intensive field studies' to understand the elements of Indian social life such as varna, family, caste, caste-system, etc. so that an assessment of new meanings of caste and scientific outlook can be presented in the future of rural life.
Caste in Modern India and Other Essays
Keywords: Telugu